Existe diferença no desempenho motor grosso de crianças escolares com e sem disfunções do trato urinário inferior? - Barbieri, Sabrina Orlandi (2024)
Studies that propose identifying lower urinary tract dysfunctions (LUTD) and comparing them to gross motor performance are scarce. In this context, the present study aimed to compare the gross motor performance of school children with and without LUTD, seeking to contribute to the clinical practice of professionals who work with this population. This research has an observational, cross-sectional design, comparing two groups, and uses a quantitative approach. 77 children and their guardians participated in the study, divided into 2 groups: children with urinary symptoms (GD) (n=34) and children without urinary symptoms (CG) (n=43). After signing the Informed Consent Form (TCLE), those responsible responded to a questionnaire to identify the sample and the Dysfunctional Voiding Symptom Score (DVSS). The children answered a questionnaire to characterize their eating and urinary habits, the DVSS and the children in the CG also completed the PINQ-br to assess quality of life (QoL). Anthropometric measurements were taken and the Gross Motor Development Test (TGMD-3) was applied to assess gross motor performance. Categorical variables were analyzed descriptively using simple frequencies and percentages and numerical variables using position and dispersion measurements. The normality of quantitative variables was assessed using the Kolmogorov-Smirnov test. The Independent Measures t Test (for variables with normal distribution) or the Mann Whitney U Test (for variables with non-normal distribution) was used to compare the GD and CG groups and the total GMI score of the TGMD-3. . Inter-rater reliability was analyzed using the intraclass correlation coefficient (ICC) (ICC ≥ 0.7) considering the data reliable. The agreement rate of parents' and children's DVSS responses was also assessed using the ICC. P<0.05 was adopted as statistical significance in all tests. The results revealed a prevalence of 44.16% of children with LUTD, and no agreement was observed between the DVSS scores of guardians and children (ICC=0.247). The children in the DG showed a mild impairment in QoL. Furthermore, the GD demonstrated lower motor performance compared to the CG. These findings indicate that school children with LUTD may have impaired motor performance compared to the control group.